Papers in linguistics - Hiremath, Rudrayya Chandrayya, 1922-; Sunkapur, M. S.; Kulli, Jayavant S. (Research series (Mysore, India) ;, 1981)
Festschrift honoring Rudrayya Chandrayya Hiremath, b. 1922, Kannada linguist and critic.